Continuous noninvasive cardiac output in children: is this the next generation of operating room monitors? Initial experience in 402 pediatric patients. Issue 2 (10th June 2014) - Coté, Charles J.; Sui, Jinghu; Anderson, Thomas Anthony; Bhattacharya, Somaletha T.; Shank, Erik S.; Tuason, Pacifico M.; August, David A.; Zibaitis, Audrius; Firth, Paul G.; Fuzaylov, Gennadiy; Leeman, Michael R.; Mai, Christine L.; et al.
Summary Background Electrical Cardiometry™ (EC) estimates cardiac parameters by measuring changes in thoracic electrical bioimpedance during the cardiac cycle. The ICON®, using four electrocardiogram electrodes (EKG), estimates the maximum rate of change of impedance to peak aortic blood acceleration (based on the premise that red blood cells change from random orientation during diastole (high impedance) to an aligned state during systole (low impedance)). Objective To determine whether continuous cardiac output (CO) data provide additional information to current anesthesia monitors that is useful to practitioners. Methods After IRB approval and verbal consent, 402 children were enrolled. Data were uploaded to our anesthesia record at one‐minute intervals. Ten‐second measurements (averaged over the previous 20 heart beats) were downloaded to separate files for later comparison with routine OR monitors. Results Data from 374 were in the final cohort (loss of signal or improper lead placement); 292 012 measurements during 58 049 min of anesthesia were made in these children (1 day to 19 years and 1 to 107 kg). Four events had a ≥25% reduction in cardiac index at least 1 min before a clinically important change in other monitored parameters; 18 events in 14 children confirmed manifestations of other hemodynamic measures; eight events may have represented artifacts because the observed measurements did not seem to fit the clinical parameters of the other monitors; three other events documented decreased stroke index with extreme tachycardia. Conclusions Electrical cardiometry provides real‐time cardiovascular information regarding developing hemodynamic events and successfully tracked the rapid response to interventions in children of all sizes. Intervention decisions must be based on the combined data from all monitors and the clinical situation. Our experience suggests that this type of monitor may be an important addition to real‐time hemodynamic monitoring.